THE INFLUENCE OF PRINCIPALS’ MANAGERIAL SKILLS AND SCHOOL CLIMATE ON TEACHER PERFORMANCE IN PUBLIC JUNIOR HIGH SCHOOLS IN PULAU HARUKU DISTRICT - Muhammad Nur Fauzi Angkotasan; Tanwey. G. Ratumanan; Lambertus J. Lokollo (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of principals’ managerial skills and school climate on teacher performance at public junior high schools in Pulau Haruku District, Central Maluku Regency. This research employed a quantitative method, with data collected through questionnaires. The research sample consisted of 3 principals and 89 teachers from five public junior high schools. Data analysis was conducted using descriptive statistics and multiple linear regression with the assistance of SPSS. The results showed that principals’ managerial skills were in the very high category (46%), school climate was in the high category (42%), and teacher performance was in the very high category (54%). Partially, principals’ managerial skills had a significant effect on teacher performance, contributing 25.5%, while school climate also had a significant effect, contributing 59.9%. Simultaneously, both variables had a significant effect on teacher performance, with a contribution of 65.7%. These findings indicate that improving principals’ managerial abilities and creating a conducive school climate can enhance teacher performance.